First record of the Sikkim wolf snake Lycodon gammiei (Blanford, 1878), (Reptilia, Squamata, Colubridae) in Nepal - Subba, Asmit; Kunwar, Nischal; Angdembe, Nirjal; Limbu, Sivaraj; Khanal, Laxman (Nepalese Journal of Zoology, 2025)
The genus Lycodon (Reptilia, Squamata, Colubridae) comprises nocturnal and non-venomous to mild-venomous snakes represented by 82 described species globally. In Nepal, three species of Lycodon- Lycodon aulicus, L. jara and L. striatus have been documented to date. This study reports the first confirmed occurrence of the Sikkim wolf snake (L. gammiei) in Nepal, based on a road-killed specimen recorded at Miklajung Rural Municipality, Panchthar District in eastern Nepal. Morphological examination (scale counts, coloration, pattern) confirmed identity and distinguished it from sympatric congeners.  L. gammiei, so far known to be endemic to the Eastern Himalayas, has previously been documented only in Sikkim, India, and adjacent regions. The discovery extends the species' known range westward by approximately 150–200 km, highlighting the eastern Himalayan foothills as a potential dispersal corridor. This finding underscores the region's cryptic herpetofaunal diversity. It further emphasizes the importance of targeted surveys and conservation measures to mitigate potential threats arising from the habitat modification and human activities.